2014
DOI: 10.1371/journal.pgen.1004078
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleus Genome Sequencing Reveals High Similarity among Nuclei of an Endomycorrhizal Fungus

Abstract: Nuclei of arbuscular endomycorrhizal fungi have been described as highly diverse due to their asexual nature and absence of a single cell stage with only one nucleus. This has raised fundamental questions concerning speciation, selection and transmission of the genetic make-up to next generations. Although this concept has become textbook knowledge, it is only based on studying a few loci, including 45S rDNA. To provide a more comprehensive insight into the genetic makeup of arbuscular endomycorrhizal fungi, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
334
0
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(359 citation statements)
references
References 94 publications
22
334
0
3
Order By: Relevance
“…This gene count is in line with the about 28 000 genes reported for R. irregularis, the closest relative of G. margarita so far sequenced (Tisserant et al, 2013;Lin et al, 2014). The G. margarita transcripts had an average GC content of 31.96%, a median contig length of 781 bp, and an average contig length of 1185.77 bp; the contig N50 based on all transcripts was 1683 bp.…”
Section: Resultssupporting
confidence: 86%
“…This gene count is in line with the about 28 000 genes reported for R. irregularis, the closest relative of G. margarita so far sequenced (Tisserant et al, 2013;Lin et al, 2014). The G. margarita transcripts had an average GC content of 31.96%, a median contig length of 781 bp, and an average contig length of 1185.77 bp; the contig N50 based on all transcripts was 1683 bp.…”
Section: Resultssupporting
confidence: 86%
“…This attempt to understand the phosphate sensing and signaling mechanisms in G. margarita has revealed the presence of common and novel components of the canonical PHO and PKA pathways in this AM fungus. In this study, the comparison of PHO and PKA pathways in R. irregularis and G. margarita ( Tisserant et al, 2012, Lin et al, 2014and Salvioli et al, 2016 further demonstrate that most components are shared between the two species. Comparative transcriptomic analyses of G. margarita and R. irregularis suggest that the core components of the PHO and PKA pathways are highly conserved across glomeraceous AM fungi.…”
Section: Conservation Of Pho and Pka Pathways In Am Fungi And Dual Rosupporting
confidence: 58%
“…ERM of G. margarita was produced in the bicompartmental system ( Maldonado-Mendoza et al, 2001). R. irregularis DAOM 197198 was used in this study to clone the GiPT2 and GiPT4 genes, which encode two low-affinity Pi transporters the Na+/Pi symporter Pho87p and Pho91p, respectively ( Tisserant et al, 2012 andLin et al, 2014). Saccharomyces cerevisiae strain S288C was employed for the isolation of Pi sensor gene pho84.…”
Section: Biological Materialsmentioning
confidence: 99%
“…However, molecular information on the involved genes is limited to yeast, and the description of the pathways leading to the different fungal ASC analogues is incomplete (Wheeler et al 2015). Since at least two enzymes, D-arabinono-1,4-lactone oxidase (ALO1) and L-gulonolactone oxidase (GULO), are known to be involved in ascorbate biosynthesis in fungi, as a first step we used TBLASTN to look for homologues in the transcriptome of R. irregularis (Tisserant et al 2013;Lin et al 2014) and of G. margarita (Salvioli et al2016). We found that G. margarita has distinct transcripts as homologues for the two genes, but R. irregularis has one homologue that matched both GULO and ALO1 (Table S5).…”
Section: Glutathione and Ascorbate Content Analysismentioning
confidence: 99%